THE NEXUS BETWEEN INVESTORS’ SENTIMENT AND HEDGE FUNDS RISK PREMIUMS - VODĂ, Tudor-Ovidiu (Studia Universitatis Babeș-Bolyai Oeconomica, 2024)
In this study, we analyzed how the systematic risk of hedge funds affects different portfolio strategies. Using monthly returns data from a sample of developed market hedge funds grouped by five strategies, we identified the systematic factors influencing returns variation from January 2003 to December 2023. Market, size effect, momentum, investment effect, and bond spread were found to be the main risk factors explaining hedge fund returns dynamics. We proposed an enhanced version of the Fung and Hsieh (2004a) model, which demonstrated improved representativity with Baker and Wurgler sentiment index included as a risk premium. The quantile regression revealed that for most strategies, the estimated models performed better for the bottom quantiles. JEL Classification: G11, G12, C58